АНАЛИЗ МОЩНОСТИ РАССЕИВАНИЯ ТРАНЗИСТОРНЫМ КЛЮЧОМ В ПОСЛЕДОВАТЕЛЬНЫХ ИМПУЛЬСНОМ И КВАЗИРЕЗОНАНСНОМ ПРЕОБРАЗОВАТЕЛЯХ - Городний , А.Н. (Інститут електродинаміки НАН України, Київ, 2012)
The results of calculating losses in electronic snitch in sequential type snitched-mode and zero current sn itch quasi-resoncmt power converters, which operate with stable voltage, are shown. Methodic of losses calculation in electronic switch with considering its parasitical parameters is proposed Equivalent simplified circuits of converters during all phases of operating are composed. In appliance with those circuits dynamic and static losses in electronic switch are calculated This analysing had implemented in wide range operating frequencies of converters. The considerable efficiency of energy performance of sequential quasi-resonant compared to pulse converters are shown. References 5, table 1, figures 5.